Papillary Carcinoma Arising From Infrahyoid Ectopic Thyroid Tissue with Hemi-agenesis of Thyroid Gland and Follicular Adenoma with Hürthle Cell Changes in Existing Thyroid Lobe: A Rare Case Report - Chowdhury, Md Sunny Anam; Awal, Md Abdul (Bangladesh Journal of Nuclear Medicine, 2018)
Ectopic thyroid tissue is a rare developmental abnormality. An ectopic thyroid tissue can be subject to various pathological processes as normal thyroid tissue including tumorigenesis. This reported case is an extremely rare case of papillary thyroid carcinoma arising from infrahyoid ectopic thyroid tissue with hemiagenesis (left lobe) of thyroid gland and presence of follicular adenoma with Hürthle cell changes in the normal positioned enlarged right thyroid lobe. Bangladesh J. Nuclear Med. 20(1): 59-62, January 2017